QR code security authentication attendance system (part I) - Chew, Amanda Li Xin (Nanyang Technological University, 2023)
With the advancement in technology, QR code seem to be an efficient solution for attendance taking. Data can be embedded on a single QR Code, where it includes student particulars, attendance status, and a random generated unique index number. These data are crucial information which can be used for identification and registration of attendance. On this platform, each professor will register their account once and go through a verification process through email validation. Once verified, the professor will login to the system to generate a QR code for students to scan for attendance taking in a tutorial room setting. Once a student scans the QR code, their student particulars and a random generated unique index number will be recorded in the local server. It will be updated and reflected on the platform, which will be accessible to professor for verification purposes and tracking of attendance records. This system is developed for the Final Year Project, and it serve as an attendance taking platform specified for professor to keep track of attendance for various assigned classes. Each professor is tasked to generate a simplified QR code, where attendance will be updated based on student inputs via the scanning of QR code. The attendance list will be available for viewing and downloading after each class ended.